Day services partnership working. Issue 2 (1st September 2011) - Johnson, Wendy; Sinclair, Jane; Reeder, Sally
Abstract : St. John's Hospice - Lancaster, serves patients within its Community for palliative and end of life care. Despite not being set up specifically for cancer patients, the hospice services are predominantly accessed by cancer patients. The Day hospice services have recently undertaken a number of initiatives to try to encourage wider access by long term conditions patients. The first success was a 'One Stop Multi-disciplinary Clinic' for motor neuron disease patients. Here patients are able to see members of the Multi-disciplinary team and the Nurse Specialist at a single hospice based clinic. Following this success the team were keen to extend the services to other long term condition groups. Initiated by a a meeting with the Parkinson's Disease Society – including some of their patients – it was agreed to host their support group which would include a weekly gentle exercise group. This commenced following a launch day. The Day Hospice more recently piloted a Chronic Obstructive Pulmonary Disease (COPD) programme. The aim being to empower patients and help them gain control of their situation as they experienced disease progression. The programme which was done in partnership with the COPD specialist acute team and the hospice team set out a 6 week programme where patients were offered information, time and support. They dealt with issues such as fatigue, breathing exercises and discussed concerns around Preferred Priorities of Care and Advanced Care Planning using a multi-disciplinary approach. All the initiatives were matched against the QIPP agenda. Following the COPD programme five of the nine patients have accessed the day hospice. The staff and volunteers within the hospice have gained education from the specialists involved and each of the stakeholders/partners have had positive feedback from the users of the services. Moreover patients are also being introduced to other services within the hospice.